Hubungan Antara Kejadian Ketuban Pecah Dini (KPD) pada Ibu Bersalin dengan Kejadian Asfiksia di Puskesmas Bantarujeg Kabupaten Majalengka - Iis, Iis; Rohaeni, Ela; Afifah, Laela Latifatul (NHM PRESS, 2024)
Premature rupture of membranes (PROM) is the rupture of the membranes before the labor process takes place. PROM is one of the factors causing neonatal asphyxia. Neonatal asphyxia occurs due to disruption of O2 exchange from the mother to the fetus. This study aims to determine the Relationship Between the Incidence of Premature Rupture of Membranes (PROM) in Mothers Giving Birth and the Incidence of Asphyxia in the Bantarujeg Health Center Work Area, Majalengka Regency. The research design used analytical and cross-sectional designs. Data collection in this study used delivery report data using a checklist. Sampling used a random sampling technique using a sample of 78 respondents of fertile women. Data processing in the study used univariate analysis and bivariate analysis with the Pearson Chi-Square Statistical test method. The results of the study showed that out of 78 respondents, 22 people (28.2%) experienced PROM, 24 newborns (30.8%) experienced asphyxia and a p value of 0.001 <0.05 was obtained. It is concluded that there is a relationship between Premature Rupture of Membranes (PROM) in Women Giving Birth and Asphyxia Incidents. It is expected that health workers, especially midwives, will participate more actively in providing holistic care to women about Premature Rupture of Membranes both during primary obstetric services and collaboration.